2020
DOI: 10.1016/j.yjsbx.2020.100034
|View full text |Cite
|
Sign up to set email alerts
|

An allosteric pocket for inhibition of bacterial Enzyme I identified by NMR-based fragment screening

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…178 STD NMR protocols and theoretical modeling have been extensively developed and tested for screening projects aimed at identifying ligands for protein drug targets. 177,[181][182][183] More recently, several STD NMR applications to the investigation of NP adsorption have appeared in the literature. For example, STD NMR has been used to screen libraries of small molecules against NP targets, 184,185 to determine the affinities of NP-ligand adducts, 184,186 and to investigate the forces driving small molecule adsorption.…”
Section: Saturation Transfer Methodsmentioning
confidence: 99%
“…178 STD NMR protocols and theoretical modeling have been extensively developed and tested for screening projects aimed at identifying ligands for protein drug targets. 177,[181][182][183] More recently, several STD NMR applications to the investigation of NP adsorption have appeared in the literature. For example, STD NMR has been used to screen libraries of small molecules against NP targets, 184,185 to determine the affinities of NP-ligand adducts, 184,186 and to investigate the forces driving small molecule adsorption.…”
Section: Saturation Transfer Methodsmentioning
confidence: 99%
“…Considering the reasons outlined in the introductory paragraphs, the trend over the past few years has been to identify PCs that bind to alternative sites of proteins rather than competing with the known ligand [ 20 ]. This can be experimentally achieved by, e.g., the use of molecular probes like in the multiple solvent crystal structure (MSCS) X-ray diffraction technique [ 108 , 109 , 110 ] or fragment-based NMR [ 111 , 112 ]. Alternative binding sites can also be discovered using bioinformatics tools mapping the surface/volume of a protein structure, allowing the search to be expanded to modeled proteins.…”
Section: Pocket Prediction Toolsmentioning
confidence: 99%
“…The phosphorylation state of EI dictates the phosphorylation state of all other downstream components of the PTS ( Deutscher et al, 2014 ) and malfunction of EI has been linked to reduced growth-rate and attenuated virulence in several bacterial species ( Edelstein et al, 1999 ; Jones et al, 2000 ; Lau et al, 2001 ; Kok et al, 2003 ). Given its central role in controlling bacterial metabolism, EI has been proposed as a target for antimicrobial design ( Kok et al, 2003 ; Huang et al, 2013 ; Nguyen and Venditti, 2020 ) or for metabolic engineering efforts aimed at developing more efficient systems for microbial production of chemicals from biomass feedstocks ( Doucette et al, 2011 ; Venditti et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coupling NMR relaxation experiments with Small Angle X-ray Scattering, we showed that binding of PEP results in further quenching of μs-ms dynamics at the EIC catalytic loops that triggers the open-to-close interdomain rearrangement and activates EI for catalysis ( Venditti et al, 2015b ). Finally, by combining NMR with Molecular Dynamics (MD) simulations, we noticed that residual conformational heterogeneity at the EIC active site in the activated enzyme-substrate complex determines the enzymatic turnover ( Dotas et al, 2020 ) and that perturbing conformational dynamics at the active site loops is an effective strategy to inhibit the phosphoryl-transfer reaction ( Nguyen and Venditti 2020 ).…”
Section: Introductionmentioning
confidence: 99%